Effects of long-acting somatostatin analogues on adrenal growth and phosphoribosyl pyrophosphate formation in experimental diabetes - Kunjara, Sirilaksana (Blackwell Publishing Ltd, 2012)
Adrenal growth and increased adrenal function occur in experimental diabetes. Previously, we have shown that phosphoribosyl pyrophosphate (PRPP) and PRPP synthetase increased rapidly between 3 and 7 days after induction of diabetes with streptozotocin (STZ), with less marked changes in enzymes of the pentose phosphate pathway. The present study examines the earlier phase of 1–3 days following induction of diabetes, seeking to elucidate whether control of PRPP production is a result of diabetic hyperglycaemia, or to a more general re-ordering of hormonal factors. To investigate this question, the role of insulin and two different long-acting somatostatin analogues, Angiopeptin and Sandostatin, were used in a well-established animal model. PRPP was chosen specifically as a target for these studies in view of its central role in nucleotide formation and nicotinamide mononucleotide synthesis via Nampt which is the rate-limiting step in the synthesis of NAD and which has been shown to have multiple roles in cell signalling in addition to its known function in glycolysis and energy production. Treatment with the somatostatin analogues ab initio effectively abolished the adrenal growth, the increase in PRPP formation and the rise of PRPP synthetase activity in the first 7 days of diabetes, without having any significant effect on blood glucose values. This suggests that elevated glucose per se is not responsible for the diabetic adrenal hypertrophy and implies that growth factors/hormones, regulated by somatostatin analogues, play a significant role in adrenal growth processes.